Use of 1-Adamantanecarboxylate as Desorbing Displacer for Eluting Solutes Retained with the Sorbent of b-Cyclodextrin Bonded Silica in Coupling Solid Phase Extraction with Micellar Electrokinetic Chromatography - Wang, D.; Wang, T.L.; He, H.B. (Asian Journal of Chemistry, 2012)
Use of 1-adamantanecarboxylate as desorbing displacer for eluting solutes retained with the sorbent of b-cyclodextrin bonded silica in coupling solid phase extraction with micellar electrokinetic chromatography was studied. The sorbent showed strong capacity of retaining 4-tert-butylphenol and 2,2-di(4-hydroxyphenyl)propane spiked in double-distilled water. Using the desorbing displacer of 1-adamantanecarboxylate was more effective in eluting 4-tert-butylphenol and 2,2-di(4-hydroxyphenyl)propane retained from the b-cyclodextrin bonded silica sorbent in the solid phase extraction cartridges than common organic solvents. The eluate collected can be directly introduced to micellar electrokinetic chromatography for separation. The results of evaluation on analytical performance of coupling the solid phase extraction with micellar electrokinetic chromatography have been presented.